2019
DOI: 10.1038/s41598-019-44987-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of enriched rare variants in JPH2-encoded junctophilin-2 among Greater Middle Eastern individuals reveals a novel homozygous variant associated with neonatal dilated cardiomyopathy

Abstract: Junctophilin-2 (JPH2) is a part of the junctional membrane complex that facilitates calcium-handling in the cardiomyocyte. Previously, missense variants in JPH2 have been linked to hypertrophic cardiomyopathy; however, pathogenic “loss of function” (LOF) variants have not been described. Family-based genetic analysis of GME individuals with cardiomyopathic disease identified an Iranian patient with dilated cardiomyopathy (DCM) as a carrier of a novel, homozygous single nucleotide inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Various types of deficits in members of the junctophilin gene family have been associated with several inherited disorders. Autosomal-dominant and recessive variants in JPH2 have been linked to hypertrophic and dilated cardiomyopathy, respectively ( 180 , 181 ). JPH1 has been revealed as a modifier gene of a hereditary motor and sensory neuropathy known as Charcot-Marie-Tooth disease ( 182 ).…”
Section: Inherited Diseases Caused By Junctophilin Gene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of deficits in members of the junctophilin gene family have been associated with several inherited disorders. Autosomal-dominant and recessive variants in JPH2 have been linked to hypertrophic and dilated cardiomyopathy, respectively ( 180 , 181 ). JPH1 has been revealed as a modifier gene of a hereditary motor and sensory neuropathy known as Charcot-Marie-Tooth disease ( 182 ).…”
Section: Inherited Diseases Caused By Junctophilin Gene Variantsmentioning
confidence: 99%
“…These variants are all predicted to truncate the JPH2 protein and have a severe loss-of-function phenotype. Jones et al ( 181 ) recently reported one of these pLOF variant (Glu641Ter) in 2 Iranian families. One proband who was homozygous for this variant was diagnosed at 20 mo of age with DCM.…”
Section: Inherited Diseases Caused By Junctophilin Gene Variantsmentioning
confidence: 99%
“…In addition to the change in JP2 expression level related to disease, according to the gene analysis results in patients with heart diseases, it has been confirmed that there are gene mutations in JP2 in some heart diseases, such as S101R, Y141H, T161L, S165F, and E169K mutations in the MORN region; A399S, 403S, and A405S mutations in the α-helix structure; and R436C and G505S mutations in the divergent domain [74][75][76][77][78][79].…”
Section: Jp2-related Diseases and Jp2 Dysregulation Mechanismsmentioning
confidence: 90%
“…Junctophilin-2 is required to maintain T-tubule structure, RyR2 function, and is a requisite component of the excitation-contraction coupling machinery (Van Oort et al, 2011;Chen et al, 2013;Guo et al, 2014;Zhang et al, 2014). Not surprisingly, mutations in junctophilin-2 are associated with cardiomyopathy, arrhythmia, and heart failure (Beavers et al, 2013;Takeshima et al, 2015;Vanninen et al, 2018;Jones et al, 2019). Junctophilin-2 is a large, nearly 700 amino acid, predominantly cytoplasmic protein containing N-terminal MORN domains that associate with the plasma membrane and a C-terminal transmembrane domain embedded in the SR (Takeshima et al, 2015; Figure 2).…”
Section: Junctophilin-2mentioning
confidence: 99%